Apakah Prinsip Syariah Mampu Menstabilkan Pasar UMKM Analisis Atas Teori Permintaan dan Penawaran Islami - Hudaa Ariiqoh (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the extent to which Sharia principles can stabilize the micro, small, and medium enterprises (MSME) market through the framework of Islamic demand and supply theory. In conventional economic systems, price fluctuations and market instability are common challenges for MSMEs. In contrast, Islamic economics offers a value-based approach that emphasizes honesty, justice, the prohibition of exploitation, and the concept of fair pricing (tsaman al-mitsli). This research employs a library research method by reviewing primary and secondary sources, including scholarly journals, classical Islamic economic texts, and recent empirical studies. The findings indicate that implementing Sharia principles fosters market stability through the reinforcement of business ethics, transparent information, and the utilization of Islamic instruments such as zakat, infaq, and profit-sharing-based financing. Furthermore, the concept of barakah (blessing) in transactions strengthens consumer loyalty and business resilience. This study concludes that Sharia principles are not only normative but also practical and strategic in addressing the challenges of market instability in the MSME sector. However, this research is limited to theoretical analysis and lacks empirical field data; therefore, future research employing quantitative or case study approaches is strongly recommended.